Mums on the Move: A pilot randomised controlled trial of a home-based physical activity intervention for mothers at risk of postnatal depression. (February 2021) - Teychenne, Megan; Abbott, Gavin; Stephens, Lena D.; Opie, Rachelle S.; Olander, Ellinor K.; Brennan, Leah; van der Pligt, Paige; Apostolopoulos, Maria; Ball, Kylie
Abstract: Background: Postnatal women are commonly physically inactive, and, when coupled with depressive symptoms, barriers to physical activity can be heightened. This study aimed to 1) examine the feasibility and acceptability of a multi-component home-based physical activity intervention delivered to mothers at risk of postnatal depression, and 2) examine changes in health behaviours (physical activity, sedentary behaviour, sleep, diet) and indicators of mental health. Methods: Sixty-two mothers (3 – 9 months postpartum) who at baseline were insufficiently active and experiencing heightened depressive symptoms were recruited into a 12-week randomised controlled trial in 2018. Participants were randomised into either a) Intervention group (receiving a theoretically underpinned multi-component program including free exercise equipment at home, access to smartphone web-app, and an online forum); or b) Control group (usual routine). Primary outcomes were program feasibility and acceptability. Secondary outcomes included self-reported and accelerometer-assessed physical activity and sedentary behavior, sleep, diet, determinants of physical activity, and mental health (depressive and anxiety symptoms), measured at baseline and follow-up (12-weeks), with self-reported physical activity, sedentary behaviour and depressive symptoms also measured at weeks 4 and 8. Qualitative data was analysed following inductive content analysis, and quantitative data using linear mixed models. Results: Exercise equipment use in the home was shown to be a feasible strategy to re-engage postnatal women in physical activity. Other components of the program (e.g. web-app, online forum) had low compliance. The program had high acceptability, predominately due to its accessibility, flexibility and ability to overcome key barriers to physical activity. The program resulted in improvements in short-term self-reported physical activity (increased 162min/week at 4 weeks, 95% CI: 37.7, 286.2), behavioural skills (B=0.4, 95% CI: 0.0, 0.8) and perceived barriers to physical activity. However, accelerometer measured physical activity decreased in the intervention group, compared to control group at week 12 (B=-1.3, 95% CI:-2.5, -0.1). There were no changes in other outcomes. Conclusions: A home-based physical activity program involving free exercise equipment is acceptable and feasible amongst women experiencing heightened postnatal depressive symptoms. Such programs may be effective in increasing engagement in physical activity, yet additional strategies may be needed to enhance maintenance of physical activity and improvements in mental health.